2015
DOI: 10.7314/apjcp.2015.16.16.7031
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of L-Arginine-Arginase Metabolic Pathway Enzymes: Immunocytochemistry and mRNA Expression in Peripheral Blood and Tissue Levels in Head and Neck Squamous Cell Carcinomas in North East India

Abstract: Background: Arginine may play important roles in tumor progression by providing ornithine for polyamine biosynthesis, required for cell growth. The aim of this work was to determine the expression of arginine metabolic pathway enzymes in head and neck squamous cell carcinoma (HNSCC) in northeast India. Materials and Methods: The expressions of arginase isoforms (ARG1 and ARG2), ornithine aminotransferase (OAT) and ornithine decarboxylase (ODC) were examined in fifty paired HNSCC and adjacent non-tumor tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
(37 reference statements)
2
6
0
Order By: Relevance
“…Similar results were observed in patients with colorectal cancer, where a higher ARG1 mRNA level was associated with worse OS and disease-free survival (DFS) [62], or classic Hodgkin lymphoma, where an elevated level of ARG1 negatively influenced PFS [37]. The overexpression of ARG1 in HNSCC tissue and peripheral blood compared to healthy donors was described by Shrivastava et al [63], but opposite results were shown by Ohashi et al [57]. Both studies did not address tumor etiology or prognosis, which may explain the discrepancy of the results.…”
Section: Discussionsupporting
confidence: 80%
“…Similar results were observed in patients with colorectal cancer, where a higher ARG1 mRNA level was associated with worse OS and disease-free survival (DFS) [62], or classic Hodgkin lymphoma, where an elevated level of ARG1 negatively influenced PFS [37]. The overexpression of ARG1 in HNSCC tissue and peripheral blood compared to healthy donors was described by Shrivastava et al [63], but opposite results were shown by Ohashi et al [57]. Both studies did not address tumor etiology or prognosis, which may explain the discrepancy of the results.…”
Section: Discussionsupporting
confidence: 80%
“…Firstly, we show that ARG1, the enzyme responsible for the catabolism of arginine, is not expressed by oral tongue cancer cells. Although this contradicts one previous study [ 12 ], it corroborates various other findings [ 13 , 14 , 15 ] and supports the hypothesis that arginine metabolism is selectively rewired in oral tongue cancer cells to create a survival advantage. Considering the lack of expression of ARG1 , we next sought to determine whether oral tongue cancer cells had adapted to function and proliferate without relying on arginine catabolism.…”
Section: Discussionsupporting
confidence: 67%
“…Aggregated results from one previous report hinted that ARG1 protein expression was higher in head and neck tumor tissues compared with nontumor [ 12 ]. However, these findings are opposite to our more recently published data [ 13 ] and two independent datasets (GEO (U133Plus2 GPL570) and TCGA) ( Figure 1 a) [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Because arginase-1 expression is usually retained in hepatocellular carcinoma, a cancer derived from hepatocytes, the immunohistochemical detection of arginase expression is commonly used to support the difficult distinction of hepatocellular carcinoma from cholangiocellular carcinoma and metastases to the liver [ 5 ]. This procedure is supported by more than 20 studies demonstrating arginase-1 expression in 80–100% of hepatocellular carcinomas [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 77%